2005
DOI: 10.1007/s00421-005-1334-3
|View full text |Cite
|
Sign up to set email alerts
|

Do blood cells mimic gene expression profile alterations known to occur in muscular adaptation to endurance training ?

Abstract: Exercise is known to upregulate mRNA synthesis for carnitine palmitoyl transferase1 (CPT1) and possibly also other mitochondrial carnitine acyltransferases in muscle tissue. The aim of this study was to test whether such an adaptation of oxidative metabolism in skeletal muscle is a systemic process and consequently, also affects other cells. Messenger RNA levels of five genes [carnitine palmitoyl transferases 1 and 2 (CPT1 and CPT2), carnitine acetyltransferase (CRAT), carnitine palmitoyltransferase 2 (CPT2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 35 publications
3
15
1
Order By: Relevance
“…As suggested by a past study performed on rats adapted to chronic hypobaric hypoxia, the mechanism of HIF-1 gene activation depends on the diVerences in vascular perfusion and oxygen-carrying functions particular to the tissue being studied . This diVerence in RNA regulation between muscle and blood compartment contradicts previous Wndings reporting similar adaptations (correlations) in serum and muscle with exercise in normoxia (Zeibig et al 2005). Indeed, the authors found a concomitant stimulation of Wve genes in blood cells and muscle tissue after a period of endurance training.…”
Section: Hif Mrna In Human Leukocytes and Skeletal Musclecontrasting
confidence: 52%
See 2 more Smart Citations
“…As suggested by a past study performed on rats adapted to chronic hypobaric hypoxia, the mechanism of HIF-1 gene activation depends on the diVerences in vascular perfusion and oxygen-carrying functions particular to the tissue being studied . This diVerence in RNA regulation between muscle and blood compartment contradicts previous Wndings reporting similar adaptations (correlations) in serum and muscle with exercise in normoxia (Zeibig et al 2005). Indeed, the authors found a concomitant stimulation of Wve genes in blood cells and muscle tissue after a period of endurance training.…”
Section: Hif Mrna In Human Leukocytes and Skeletal Musclecontrasting
confidence: 52%
“…Furthermore, the subjects followed a low-intensity training program. Given the diVerences between biopsy sampling protocols do not justify the discrepancy, the present results suggest the relationships identiWed by Zeibig et al (2005) are not universally valid for training eVects. The current results indicate a rejection of the proposed use of RNA measures in blood as a replacement of muscle biopsies for diagnostic measures on muscle adaptations to exercise.…”
Section: Hif Mrna In Human Leukocytes and Skeletal Musclementioning
confidence: 56%
See 1 more Smart Citation
“…As previously shown, PBMCs mimic mitochondrial gene expression profile alterations in muscle after 6 months of endurance training in young athletes [11]. Moreover, fasting has a profound effect on gene expression in PBMCs, in particular on PPARα [17,18].…”
Section: Introductionmentioning
confidence: 74%
“…This has been shown in distinct models of glucose intolerance like aging, high-fat feeding and genetic diabetes [6]. In cell culture experiments, in animal studies, as well as in human trials we demonstrated that L -carnitine administration significantly increased the relative mRNA abundances of genes involved in fatty acid (FA) catabolism, such as carnitine palmitoyltransferases-1 (CPT1) and carnitine acetyltransferase (CrAT) [9,10,11]. CPT1 is the rate-limiting enzyme for FA oxidation in all tissues and exists in at least three isoforms, a liver form (CPT1A) expressed in liver and many other tissues, a smaller counterpart (CPT1B) found in adipose tissue, testis, cardiac and skeletal muscle, and CPT1C in the brain [12].…”
Section: Introductionmentioning
confidence: 99%